2023
DOI: 10.24996/ijs.2023.64.3.21
|View full text |Cite
|
Sign up to set email alerts
|

Using SWAT Model to Estimate the Water Balance of Wadi Al-Mohammadi Basin, Western Iraq

Abstract: Water balance as a technique is considered one of the means that is relied upon in solving significant hydrological problems. The soil and water assessment tool (SWAT) model was used in this study to assess the water balance in the Wadi Al-Mohammadi basin located at the eastern edge of the Western Desert. Digital elevation model, soil data, Land use - Land cover, and climate data represent the most important requirements for the SWAT model's input as a database. The Wadi Al-Mohammadi basin delineation results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…According to (Al Kubaisi, 2008) who indicated that the intervals of the trend of the center of the depositional basin through Erbil basin had a thickness of about 3048 m. Also, the sediment was composed of the (siltstone, sandstone, and conglomerate) this occurred during the upper Miocene, Pliocene and Pleistocene, an uplift with intensive folding and thrusting and concurrent subsidence of deep basins had occurred in North and North East of Iraq, see Figure 3:…”
Section: Hydrogeological Conditions Of the Study Areamentioning
confidence: 99%
“…According to (Al Kubaisi, 2008) who indicated that the intervals of the trend of the center of the depositional basin through Erbil basin had a thickness of about 3048 m. Also, the sediment was composed of the (siltstone, sandstone, and conglomerate) this occurred during the upper Miocene, Pliocene and Pleistocene, an uplift with intensive folding and thrusting and concurrent subsidence of deep basins had occurred in North and North East of Iraq, see Figure 3:…”
Section: Hydrogeological Conditions Of the Study Areamentioning
confidence: 99%
“…The yearly dryness treatment was used to analyze the climatic type using equations, which Al-Kubaisi (2004) [16] devised and is based on temperature and rainfall totals: AI-1= (1*P) / (11.525*t) (t is not equal to zero) …………………………………… (5) AI-2 = 2 √P / t ……………………………………………………………………… (6) Where P is the amount of yearly precipitation (mm), t is the temperature (°C), and AI is aridity index.…”
Section: Al-kubaisimentioning
confidence: 99%
“…Rainfall occurs between November and April, with May being the exception. While, May to October months, are the hottest and with no rain [2]. In Iraq, the highest recorded temperatures vary from above 48°C in July and August to below zero °C in January [3].…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers studied the study area and its surroundings in the Western Desert, for example, [6][7][8][9][10][11]. They all had different studies on water resources, but like water harvesting, they did not mention it as a water management technique.…”
Section: Introductionmentioning
confidence: 99%